Aromatic polyethersulfone gas separation membranes - SIMMONS, JOHN WARREN (1996)
An aromatic polyethersulphone gas separation membrane comprises: (a) at least one unit of the formula (I); and (b) at least one unit derived from an aromatic dihalogenated sulphone. Also claimed is a process for separating one or more gases from a gaseous mixt. comprising bringing the mixt. into contact with the first side of a gas separation membrane in a manner to cause a portion of the mixt. to pass through the membrane to a permeate side, the resulting gas mixt. of the permeate side being enriched in one or more component over that of the mixt. of the first side. Z = 1-10C alkyl, or 6-12C aromatic; and n = 1-4.